Case Report: A rare pediatric case of paraneoplastic pemphigus associated with Castleman disease misdiagnosed as Behçets disease - Zhang, Ranran; Liu, Jia; Nie, Nana; Wang, Dahai; Wu, Jie; Zhang, Huanyu; Zhang, Ruiyun; Gao, Shan; Bai, Cui; Lin, Yi; Zhang, Qiuye; Chang, Hong (Frontiers in Pediatrics, 2024)
Castleman disease (CD) is a rare lymphoproliferative disease known as angiofollicular lymph node hyperplasia, firstly reported in 1954. It mainly occurs in adults, presenting with a wide range of clinical manifestations, including paraneoplastic pemphigus (PNP). PNP is a rare and often life-threatening autoimmune disorder characterized by painful blisters and erosions on the skin and mucous membranes. In children, PNP is often linked to Castleman disease, as evidenced in case reports. So far, less than 30 pediatric cases have been reported, with the pathogenesis remaining unclear and treatment approaches varied. Here, we present a pediatric case initially suspected as Behçet's disease due to persistent oral ulcers and conjunctivitis, and undergone a sudden aggravation of clinical features following an allergic reaction. New involvement of skin rashes and imaging findings prompted the final diagnosis as PNP linked to Unicentral Castleman disease (UCD).Through detailing the progression of clinical features and diagnostic work, we aim to arise the awareness of physicians and put emphasize on early recognition and multidisciplinary management, which can improve patient outcomes.